2008
DOI: 10.1109/tbme.2007.912404
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Total Least Squares: A New Regularization Method for the Solution of ECG Inverse Problems

Abstract: The reconstruction of epicardial potentials (EPs) from body surface potentials (BSPs) can be characterized as an ill-posed inverse problem which generally requires a regularized numerical solution. Two kinds of errors/noise: geometric errors and measurement errors exist in the ECG inverse problem and make the solution of such problem more difficulty. In particular, geometric errors will directly affect the calculation of transfer matrix A in the linear system equation AX = B. In this paper, we have applied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Due to the complexity of error sources, it is difficult to have an exact mathematic model to describe the system errors accurately. Hence we adopted the commonly used Gaussian white noise [28–30] and exponential noise to simulate the errors in matrix A , respectively.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Due to the complexity of error sources, it is difficult to have an exact mathematic model to describe the system errors accurately. Hence we adopted the commonly used Gaussian white noise [28–30] and exponential noise to simulate the errors in matrix A , respectively.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…These methods include Tikhonov regularization method [8], least squares QR (LSQR) [13], truncated total least square (TTLS) [14], Kalman filter [15], generalized minimal residual [16], and level-set [17] and statistical approaches [18]. Although incorporating the L 2-norm-based constraint handles the ill-posedness of this inverse problem and provides stability in the presence of noise, it ultimately diffuses the source reconstruction solution.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, they have proposed a novel preconditioner for the PCG method to solve (1) and a cheap iterative method such as successive overrelaxation (SOR) to further refine the solution for a desired accuracy. In 2008, Shou et al [7] have showed that the reconstruction of epicardial potentials (EPs) from body surface potentials (BSPs) can be characterized as an ill-posed inverse problem and geometric errors in the ECG inverse problem will directly affect the calculation of transfer matrix A in (1). In the field of systems and control science, Ding and Chen [8] have pointed out that Sylvester equations in systems and control especially Lyapunov equations in continuous- and discrete-time stability analysis can be converted into equivalent equations as (1).…”
Section: Introductionmentioning
confidence: 99%